Selected Chemical Properties of Necrosols from the Abandoned Cemeteries Słabowo and Szymonka (Great Mazurian Lakes District) - Majgier, Leszek; Rahmonov, Oimahmad (Bulletin of Geography. Physical Geography Series, 2012)
The paper shows the occurrences of cemetery soils and the physico-chemical features of soils in the cemeteries Słabowo and Szymonka (Great Mazurian Lakes District). Necrosols are anthropogenic soils and belong to Urbanosols. They form only in the area of cemeteries. Four soil profiles (Necrosols) were investigated in terms of morphological description and chemical properties especially phosphorus (Pt), organic carbon (OC) and nitrogen (Nt). These profiles were compared with the reference profile (Rusty soil, according to WRB 2007 Brunic Arenosol) made outside the cemetery. On the basis of research Necrosol has been defined as a soil formed by special human activity in cemeteries and burial grounds with specific soil horizon sequence, and also physical and chemical properties.